Targeted genomic surveillance unveils genetic variations linked to regional malaria drug resistance dynamics in India - Khilari, Ajinkya; Sharma, Shweta; Bajpai, Manali; Viswan, K. Anju; Chaturvedi, Rini; Mirdha, Bijay R.; Rahi, Manju; Sharma, Amit; Shanmugam, Dhanasekaran (Open Forum Infectious Diseases, 2026)
Background India has made substantial progress in reducing Plasmodium falciparum malaria cases and has set a target to eliminate malaria by 2030. Although artemisinin-based combination therapy (ACT) treatment remains effective, tracking regional differences in genetic variants associated with antimalarial resistance is required for effective drug policy implementation.Methods We analyzed 238 P. falciparum clinical samples from 6 Indian states by sequencing 15 parasite genes associated with reduced drug effectiveness. The method involved nanopore sequencing of target gene amplicons derived from dried blood spots using a highly-sensitive PfMDR15 surveillance panel.Results India's historical policy of artesunate-sulfadoxine-pyrimethamine in central India and artemether-lumefantrine in the Northeast has shaped contrasting resistance profiles. In the Northeast, chloroquine resistance persisted at high frequency (Pfcrt K76T and CVIET haplotype; Pfaat1 S258L), alongside quintuple and sextuple Pfdhfr-Pfdhps haplotypes conferring complete sulfadoxine-pyrimethamine resistance. Central India showed variable chloroquine resistance (parasites largely retained wild-type Pfcrt) and emerging lumefantrine tolerance (Pfmdr1 Y184F, Pfaat1 S258L). Interestingly, Delhi (Central India) parasites resembled profiles from the distant Northeast, which borders South East Asia. The detection of Pfaat1 S258L, previously reported only from Africa and associated with reduced lumefantrine susceptibility, suggests convergent evolution under ACT partner-drug pressure. No WHO-validated Pfk13 artemisinin resistance mutations were detected, supporting continued efficacy of ACT.Conclusions India's resistance landscape is fragmented, with signals of expanding lumefantrine tolerance and importation or evolution of globally relevant mutations. These findings highlight the importance of integrating molecular genomic surveillance into malaria control policy to monitor and protect ACT effectiveness and advance malaria elimination. Monitoring of drug resistance associated mutations in P. falciparum parasites is critical for effective drug treatment. We have demonstrated the use of a scalable genomic surveillance protocol for tracking drug resistance linked mutations in parasite genes from clinical isolates in India. The study suggests extensive regional diversity in antimalarial resistance profiles and provides the first hint of possible emergence of lumefantrine tolerance in India.
Keywords: drug resistance; malaria; Oxford nanopore; P. falciparum; pfMDR15